JAMINAN PURNA SERVICE TERHADAP KONSUMEN ATAS PRODUK RAKITAN MESIN PT.TOYOTA AUTO 2000 DIKAITKAN DENGAN KUHPERDATA JO. PASAL 25 UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Bagus Eka Saputra (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThe world's automotive technology is developing very rapidly, especially car ignition systems such as the use of platinum, CDI, and now the ECU is capable of detecting user characters and adjusting all settings needed in the car according to the user's character. This legal writing aims to find out and examine the application of Article 25 of Law Number 8 of 1999 concerning Consumer Protection in overcoming fraud in post-service guarantees carried out by business actors selling machine assembled products, and to know and review efforts to resolve disputes that occur between perpetrators business with consumers related to Toyota engine assembly products based on the provisions of Law Number 8 of 1999 concerning Consumer Protection.This type of research is empirical legal research where primary data is obtained based on research at PT Toyota Auto 2000 Samarinda Branch. And secondary data through books and laws that are relevant to research. Primary data is collected by interview and observation techniques. Then analyzed qualitatively and presented descriptivelyThe results of the study that the application of Article 25 of the Law on consumer protection among business actors in this case the dealers of machine assemblies is still not optimal because they do not understand the importance of after-service services and also often violate the rules of after-service services. Business actors producing goods whose utilization is sustainable within a time limit of at least 1 year must provide spare parts and / or after-sale facilities and must fulfill the guarantee or guarantee as agreed. Disputes that often occur between consumers and machine assemblers are in the case of violations of guarantee guarantees of 88%, while for disputes in the case of service violations the supply of spare parts is only 5% and for disputes in the case of violations of repair services or service services is only 7 % and the dispute resolution process carried out by both parties, both consumers and shop sellers of assembled computers is by taking the Non Litigation Path without going through BPSK, which is an agreement between buyers and sellers.